Formation of periodic zigzag patterns in the twist-bend nematic liquid crystal phase by surface treatment. Issue 1 (2nd January 2017) - You, Ra; Paterson, Daniel A.; Storey, John M. D.; Imrie, Corrie T.; Yoon, Dong Ki
ABSTRACT: Zigzag patterns were successfully generated in the twist-bend nematic (NTB ) phase of 1-(4-cyanobiphenyl-4′-yl)-6-(4-cyanobiphenyl-4′-yloxy)hexane (CB6OCB) via simple surface treatment. A detailed microscopy study using polarised optical microscopy and fluorescence confocal polarising microscopy was performed to observe the director arrangement in the zigzags, where distinctive periodic patterns were found to be aligned perpendicular to the rubbing direction. These patterns originate from the structural instability and generation of splay deformation with focal conic domain-like structures that are typically found in smectic phases, revealing that the NTB phase has physical properties similar to those of the smectic phase. Observation of these unusual zigzag patterns in the NTB phase opens an avenue for use of this phase in potential applications such as optical modulators and gratings. GRAPHICAL ABSTRACT: